A Profile of Social Participation in a Nationally Representative Sample of Canadian Older Adults: Findings from the Canadian Longitudinal Study on Aging. Issue 4 (28th December 2022) - Reynolds, Kristin A.; Sommer, Jordana; Mackenzie, Corey S.; Koven, Lesley
Abstract: Social participation has tremendous implications for the physical and mental health of older adults. A growing body of Canadian literature has examined social participation among older adults, including frequency of participation; gender, age, and regional differences in participation; and associations with self-perceived health, loneliness, and life dissatisfaction. The current study adds to this important body of research, using a large, nationally representative sample of adults 45–85 years of age (Canadian Longitudinal Study on Aging [CLSA] baseline data [ n = 51, 338]), to examine nuanced characteristics associated with social participation (socio-demographics, social support, cognitive ability, mental health, physical conditions), frequency of participation, and the relationship between the aforementioned characteristics and frequency of participation. Findings indicated that compared with those who reported infrequent/no participation, more frequent participation was associated with greater social support, higher cognitive abilities, increased satisfaction with life, fewer depressive symptoms, reduced odds of self-reported mood and anxiety disorders, and fewer self-reported physical conditions. Findings highlight the importance of active social participation, and have important implications for the development and implementation of accessible community programs across Canada.